Flower size affects bee species visitation pattern on flowers with poricidal anthers across pollination studies - Delgado, Tamiris [UNESP]; Leal, Laura Carolina; El Ottra, Juliana Hanna Leite; Brito, Vinicius Lourenço Garcia; Nogueira, Anselmo (Elsevier, 2023)
Flower size is a crucial trait for pollinator attraction. In flowers with poricidal anthers, the plant constraints the pollinator's access to the flower's rewards by enclosing pollen grains in poricidal anthers. The pollen is only released by mechanical vibrations applied mainly by bee species during buzz pollination. Although buzz-pollinated flowers exhibit a large size variation across species, their influence over patterns of flower visitation by different pollinator species remains to be elucidated. To fill such gap, we asked how flower size influences flower visitor assemblage, especially bees, across plant species and how flower size is related to body size and vibrating behavior of the most frequent bee species. We hypothesized that the assemblage of animals, especially bees, visiting larger flowers have higher taxonomic and functional diversity than smaller flowers, and the most frequent bee species visiting larger flowers have larger body size and a mandatory vibrating behavior. To test this hypothesis, we conducted a systematic review of pollination studies that reported patterns of flower visitation in plant species with poricidal anthers, describing the relationship between flower size and flower visitor metrics. We found that large-flowered species were visited by three times more species than small-flowered species, including vibrating and non-vibrating bee species. Unlike our expectations, non-vibrating bees were largely absent from small-flowered species. The most frequent bee species visiting flowers, irrespective of flower size, exhibited vibrating behavior. The most frequent bee species visiting large flowers were twice the body size of those visiting small flowers, highlighting a morphological match between flowers and pollinators. Although larger flowers are more susceptible to interactions with exploiters, reproductive success should be favored owing to the higher probability of their interaction with vibrating, large-bodied bee species. Still, a reduction in flower size probably prevents interactions with non-vibrating bees, while favoring vibrating small-bodied bee species.
Keywords: Bee diversity; Buzz-pollination; Flower attraction; Flower evolution; Pollen flower; Quantitative review